Collective Housing of Mice of Different Age Groups before Maturity Affects Mouse Behavior - Hiroshi Ueno; Shunsuke Suemitsu; Shinji Murakami; Naoya Kitamura; Kenta Wani; Yu Takahashi; Yosuke Matsumoto; Motoi Okamoto; Takeshi Ishihara (Behavioural Neurology)
Background. Although population housing is recommended by many animal management and ethical guidelines, the effect of collective housing of mice of different age groups on mouse behavior has not been clarified. Since the development of the central nervous system continues to occur before sexual maturation, the stress of social ranking formation among male individuals in mixed housing conditions can affect postmaturation behavior. To assess these effects, sexually immature mice of different ages were housed in the same cage and a series of behavioral tests were performed after maturation. Results. The findings for three groups of mice—junior mice housed with older mice, senior mice housed with younger mice, and mice housed with other mice of the same age—were compared. Junior mice showed higher body weight and activity as well as lower grip strength and anxiety-like behaviors than other mice. In contrast, senior mice showed lower body temperature and increased aggression, antinociceptive effect, and home-cage activity in the dark period in comparison with other mice. Conclusions. Thus, combined housing of immature mice of different age groups affects mouse behavior after maturation. Appropriate prematuration housing conditions are crucial to eliminate the uncontrollable bias caused by age-related social stratification.